Yes! There is an ethics of care: an answer for Peter Allmark. - Bradshaw, A (1996)
This paper is a response to Peter Allmark's thesis that 'there can be no "caring" ethics'. It argues that the current preoccupation in nursing to define an ethics of care is a direct result of breaking nursing tradition. Subsequent attempts to find a moral basis for care, whether from subjective experimental perspectives such as described by Noddings, or from rational and detached approaches derived from Kant, are inevitably flawed. Writers may still implicitly presuppose a concept of care drawn from the Judaeo-Christian tradition but without explicit recourse to its moral basis nursing is left rudderless and potentially without purpose. The very concept of 'care' cut off from its roots becomes a meaningless term without either normative or descriptive content.